Inducing host resistance against fusarium wilt of banana through application of chitosan - Al Hetar, Mohammed Yahya Abdullah (2013)
This study was undertaken with the aim to evaluate the effects of chitosan on the activation of defense related compounds to increase tolerance to Fusarium oxysporum f. sp. cubense Race 4 (FocR4) in susceptible banana seedlings var Berangan. In the in vitro studies, chitosan reduced the hyphal growth of FocR4 on Potato Dextrose Agar (PDA) medium and gave maximum inhibition of 76.36 % at 8 mg/ml. Inhibition of fungal growth was more efficient in Potato Dextrose Broth (PDB) where complete inhibition of mycelial growth of FocR4 was accomplished at all concentrations tested. Chitosan inhibited the sporulation of FocR4 by a maximum of 96.53 % at 8 mg/ml chitosan and 100% inhibition of spore germination was recorded at all concentrations tested. Chitosan was also found to induce morphological and cytological changes in FocR4 characterized by agglomeration of hyphae, abnormal shapes, and formation of vesicles or empty cells devoid of cytoplasm in the mycelia. Chitosan sprayed at concentrations of more than 0.3 mg/ml was found to cause damage to banana leaves. There was no significant difference in photosynthesis parameters including photosynthetic rates, stomatal conductance and chlorophyll contents within four days after spraying with chitosan at 0.3 mg/ml. However, chitosan was found to increase significantly the activities of peroxidase (PO), phenylalanine ammonia lyases (PAL), lignothioglycolic acid (LTGA), chitinases and glucanase enzymes in banana roots. The occurrence of induced resistance enhanced tolerance of the seedlings to Fusarium wilt based on parameters such as delay in onset of foliar disease symptoms, lower in percentage of disease severity (DS), lower in percentage of disease incidence (DI), area under disease progress curve (AUDPC), and epidemic rate. Vegetative growth were measured based on increased in plant height, number of leaves, diameter of pseudostem, root and shoot dry mass showing significant improvement only between treatments challenged by inoculation with FocR4 (T1 and T2). The growth of banana plants was not influenced by chitosan itself as a growth stimulator but it enhanced the growth in those infected with FocR4. The increase in PO, PAL, LTGA, chitinase and β-1,3-glucanase activity in seedlings treated with chitosan had been shown to be associated with plant defense through the decrease percentage of disease severity,disease incidence and area under disease progress curve. This indicated effective role by chitosan in controlling banana seedlings against wilt disease caused by FocR4. It showed promise as an inducer in the activation of host defense systems and increasing tolerance to FocR4 infection in susceptible banana var Berangan. Further studies regarding application frequency and combination techniques are essential to more effective of control this disease.